Longitudinal pathways from emotional abuse to problematic gaming in adolescents: The role of psychoticism - Valeria Verrastro; Valeria Saladino; Fiorenza Giordano; Danilo Calaresi (Comprehensive Psychiatry)
Background: Problematic gaming (PG) has emerged as a major concern due to its potential impact on adolescents' everyday lives. Emotional abuse (EA) and psychoticism are considered factors influencing PG, but their long-term interactions have not been extensively studied. This research investigates these relationships over time using the Interaction of Person–Affect–Cognition–Execution (I-PACE) model. Methods: The study involved 1902 Italian adolescents (mean age = 15.45, SD = 1.10) in a three-wave longitudinal study. Surveys were conducted at the beginning (T1), after six months (T2), and after twelve months (T3). Structural equation modeling (SEM) was used to evaluate bidirectional relationships and mediation effects among the variables. Results: The findings indicated that EA consistently predicted both psychoticism and PG, while psychoticism consistently predicted PG. However, psychoticism did not predict EA, and PG did not predict either EA or psychoticism. Significant mediation effects were found from EA at T1 to PG at T3 through EA at T2, psychoticism at T2, and PG at T2, as well as from psychoticism at T1 to PG at T3 through psychoticism at T2 and PG at T2. No significant indirect effect was observed from psychoticism at T2 to PG at T3 through EA at T2. Conclusions: The results suggest that adolescents experiencing EA are more prone to PG, with psychoticism worsening this effect. Effective interventions might include emotional support programs and therapies targeting psychoticism traits. Combining these approaches could improve treatment outcomes for adolescents with PG.